The Impact of Seropositivity on Systemic Bone Loss in Rheumatoid Arthritis—A 3-Year Interim Analysis of a Longitudinal Observational Cohort Study - Yu, Shan-Fu; Chen, Jia-Feng; Chen, Ying-Chou; Wang, Yu-Wei; Hsu, Chung-Yuan; Lai, Han-Ming; He, Hsiao-Ru; Ko, Chi-Hua; Chiu, Wen-Chan; Cheng, Tien-Tsai (Frontiers in Medicine, 2022)
Objective: To explore the impact of seropositivity on systemic bone loss in rheumatoid arthritis (RA). Methods: We conducted an interim analysis of the RA registry. Patients were examined with dual-energy X-ray absorptiometry at baseline and again three years later. Participants were grouped into seropositive (SPRA) and seronegative (SNRA) based on the presence or absence of rheumatoid factor (RF) and/or anti-cyclic citrullinated peptide antibodies (ACPA). After matching (1:2) for age and sex, SNRA and SPRA patients were divided into groups A and B. Each matched group (A or B) was further subdivided according to the number of antibodies present (0, group I; 1, group II; 2, group III). Multiple ordinary least squares regression was used with the dependent variables to develop a model to predict bone mineral density (BMD) change. Results: A total of 477 participants who completed a 3-year observation period were included. After matching, 312 participants were enrolled (group A, 104; group B, 208). Three years later, group B had significant BMD reduction in the femoral neck (FN) (p < 0.001), total hip (TH) (p = 0.001), and first through fourth lumbar vertebrae (L1–4) (p = 0.006), while group A had bone loss only at FN (p = 0.002). Groups I, II, and III included 104, 52, and 156 participants, respectively. Compared to baseline, BMD decreased signiﬁcantly at FN (p = 0.002) in group I, FN (p < 0.001) in group II, and FN (p < 0.001), TH (p = 0.002), and L1–4 (p = 0.016) in group III. In terms of regression-adjusted percent change in BMD, more significantly negative changes were found at all measured sites in group B (p < 0.001, all) and at TH and L1–4 within groups I-III (p for trend < 0.001 and <0.001, respectively). Regardless of antibodies, anti-osteoporotic therapy can preserve bone density in RA patients. Conclusion: After three years, SPRA patients lost more bone density than SNRA patients. More attention should be paid to SPRA patients, especially those with double-positive antibodies, including a vigorous evaluation of BMD and fracture risk. Anti-osteoporotic therapy can prevent BMD loss irrespective of autoantibodies.